Managing up : forge strong ties, set clear expectations, promote your ideas - Thomas, James Edward (20 minute manager series., 2022)
Your boss plays an important role in your career. So how do you navigate this delicate, significant professional relationship without playing political games or compromising your character? Managing Up offers concise, expert tips on: - Understanding your manager's priorities and pressures - Setting a positive tone for the relationship - Managing expectations-and egos - Earning trust and respect Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly listen to and apply, for ambitious professionals and aspiring executives-from the most trusted source in business.